2008
DOI: 10.1622/1059-8405(2008)024[0021:psfasc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Program Strategies for Adolescent Smoking Cessation

Abstract: School nurses who work with adolescents are in an ideal position to promote smoking cessation. This opportunity is important because research suggests teens who smoke are likely to become habitual smokers. This study characterizes adolescents' patterns and levels of smoking, describes adolescents' perceptions toward smoking, and delineates quit strategies that may prove helpful for adolescents who attempt smoking cessation. Results suggest adolescent smokers have highly variable patterns and levels of smoking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…It has additionally been estimated that adolescent smokers who consume a cumulative number of at least 100 cigarettes will continue to smoke for another 16-20 years (Pierce & Gilpin, 1996). Qualitative findings from a study conducted by Fritz et al (2008) found adolescents who smoke frequently fail to consider their future health and thus continue to be unaware of the harmful effects of smoking and the addictive nature of nicotine, despite efforts to educate and warn children at a young age.…”
Section: Smoking Initiation and Long-term Maintenancementioning
confidence: 99%
“…It has additionally been estimated that adolescent smokers who consume a cumulative number of at least 100 cigarettes will continue to smoke for another 16-20 years (Pierce & Gilpin, 1996). Qualitative findings from a study conducted by Fritz et al (2008) found adolescents who smoke frequently fail to consider their future health and thus continue to be unaware of the harmful effects of smoking and the addictive nature of nicotine, despite efforts to educate and warn children at a young age.…”
Section: Smoking Initiation and Long-term Maintenancementioning
confidence: 99%
“…These individuals initiate smoking at early ages, 8 inaccurately believe that they will soon stop smoking, 9 and may not consider the later harmful effects of tobacco use. 10 Approximately 21% of U.S. children ages 9 to 17 years have diagnosable mental health disorders or addictions, and 5% of these have severe functional impairments related to psychiatric disorders. 11 Anxiety disorders are the most common psychiatric diagnoses, followed by disruptive disorders and mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, Hall and Fong (2003) successfully promoted increased physical activity by having undergraduates undergo a series of learning sessions and activities meant to help them better understand the long-term consequences of their present actions. And, in an exploratory study, Fritz, Wider, Hardin, and Horrocks (2008) measured the effectiveness of an intervention meant to teach adolescents about the future consequences of smoking, finding that such information increased the desire to quit smoking. It may be fruitful, then, to encourage adaptive health behavior by inducing people to think about how their actions now will impact their lives in the future.…”
mentioning
confidence: 99%